Firm Value Volatility in View of Profit Performance and Practices Good Corporate Governance - Arifin, Andi Harmoko (Program Pascasarjana STIE Amkop Makassar, 2023)
Researchers are interested in raising this title because, by implementing good corporate governance, good financial performance will also be achieved. Where, the role of Good Corporate Governance itself is as a system of control and balance or the art of directing and controlling a company to maximize its corporate value and maintain the long-term sustainability of the company. The type of research used in this research is quantitative research in a sociative way , namely research that focuses on testing theories through measuring the relationship between variables. The population in this study were 33 Consumer Goods sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the research period (2018 – 2021). Financial performance have a positive and significant effect on firm value in consumer goods companies on the Indonesia Stock Exchange in 2018-2021, the results of the partial test of the Good Corporate Governance variable have no negative effect and not significant to company value in consumer goods companies on the Indonesia Stock Exchange in 2018 -2021. The role of Good Corporate Governance itself is as a system of control and balance or the art of directing and controlling a company to maximize its corporate value and maintain the long-term sustainability of the company Kata Kunci: Financial performance, Firm value, Good Corporate Governance